Fossil metabolism of Argentine agriculture. Keys from political ecology - Rossi, Leonardo (2025)
Introduction: While the main analyses of the environmental crisis focus on CO2 emissions from transportation systems and urban-industrial infrastructure, the agriculture and food systems are minimized within this agenda. Given its significant ecological impact and political implications, this article seeks to contribute to the research study of capitalist food metabolism focusing on the Argentine case. Objective: The work aims to review the state of the art in terms of energy consumption and ecological-climatic impacts of the agricultural export system with a focus on fertilizer and fuel consumption. Likewise, it is correlatively proposed to exhibit key features of the agrarian and export structure on which this metabolism is organized. Methodology: To operationalize the approach, we appeal to the notion of social metabolism, first reconstructing its economic-ecological aspects as ecological Marxism and explaining its relevance for the historical-global understanding of the capitalist food regime. Conclusions: From the data survey, both the scientific need and the political relevance of new and detailed metabolic analyses of the Argentine agriculture system arise, which also considers the differential responsibilities of the agents involved in its different links.